Rocuronium and sugammadex in a 3 days old neonate for draining an ovarian cyst. Neuromuscular management and review of the literature - Carlos,Ricardo Vieira (2016)
Abstract A case is reported in which a 3-days old neonate with a giant ovarian cyst was scheduled for surgery. The patient received a dose of sugammadex to reverse a rocuronium-induced neuromuscular block. A fast and efficient recovery from neuromuscular block was achieved within 90 s. No adverse events or other safety concerns were observed. Furthermore, a review of the literature on the use of sugammadex in neonates was performed.